Scavenger Hunt on Students’ English Vocabulary Mastery - Widya Widya; Siti Nurani (Universitas Bunda Mulia, 2017)
Learning vocabulary is the most fundamental aspects of learning for students in learning the language. In the process, the teacher is expected to be a good facilitator so that the vocabulary learning process can proceed smoothly. Creativity in learning vocabulary is absolutely necessary. Scavenger Hunt technique was chosen as the solution of the saturation experienced by students in the process of learning English vocabulary. The purpose of this reseach is improving the mastery and understanding of the students' vocabulary appropriate with context and function of everyday use, through the application of Scavenger Hunt technique. Moreover, this teaching technique is also expected to add a new learning experience for students. The research was carried out in Gema Insani Indonesia Foundation by employing a classroom action research with two cycles of assessments. There were 18 third grade elementary school students as an object of the research. The data was collected by observation, note taking, and test. The findings showed an increase in the ability of students’ mastery and understanding of the meaning of the vocabulary through the application of Scavenger Hunt technique that can be seen from the increase in student’s mean score on the second cycle with 82 that is considered as good predicate. Keywords: scavenger hunt, vocabulary, vocabulary learning